Kunst & Zwalm. - Courtens, Laurent; Van Den Ende, Eliane (Zwalm : vzw Boem, Christine Vermassen, 2007)
Antoinz, Elodie ; Berlanger, Marcel ; Breugelmans, Karel ; Cole, Stijn ; Cüpper, Ralph ; Cuyvers, Wim ; Derwéduwé, Yvan ; Drieghe, Noël ; Filz, Willi ; François, Eddy ; HAP ; Maes, Ives ; Mareene, Karine ; Pierson, Gauthier ; Timmermans, Ante ; Van Ingelgem, Herman ; Zéno, Thierry
boek